2022
DOI: 10.1007/s00421-022-05027-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rugby training on indirect markers of gut permeability and gut damage in academy level rugby players

Abstract: Purpose To assess indirect markers of intestinal endothelial cell damage and permeability in academy rugby players in response to rugby training at the beginning and end of preseason. Methods Blood and urinary measures (intestinal fatty acid binding protein and lactulose:rhamnose) as measures of gastrointestinal cell damage and permeability were taken at rest and after a standardised collision-based rugby training session in 19 elite male academy rugby pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…The exercise protocol test lasted 45 min and the gastrointestinal permeability markers tended to be lower after sports preparation, similarly to our results (but our test only lasted around 6 min) [ 14 ]. Chantler et al [ 14 ] suggested that improved aerobic fitness may decrease the level of splanchnic hypoperfusion. We found that for Test II, the athletes finished the exercise test in a shorter time and achieved higher power (the change did not reach significance, but at the competitive elite level of sports performance, even 1 s makes a huge difference that might change the place in the ranking).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The exercise protocol test lasted 45 min and the gastrointestinal permeability markers tended to be lower after sports preparation, similarly to our results (but our test only lasted around 6 min) [ 14 ]. Chantler et al [ 14 ] suggested that improved aerobic fitness may decrease the level of splanchnic hypoperfusion. We found that for Test II, the athletes finished the exercise test in a shorter time and achieved higher power (the change did not reach significance, but at the competitive elite level of sports performance, even 1 s makes a huge difference that might change the place in the ranking).…”
Section: Discussionsupporting
confidence: 87%
“…There are a few studies that have followed changes in gut permeability and injury markers in competitive elite athletes. Chantler et al [ 14 ] observed elite rugby players (n = 19) during 6 weeks of preseason training. The exercise protocol test lasted 45 min and the gastrointestinal permeability markers tended to be lower after sports preparation, similarly to our results (but our test only lasted around 6 min) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chantler et al (2022) observed elite rugby players (N = 19) during six weeks of preseason training, and the GI permeability markers tended to lower immediately after the exercise test con rming our outcomes (12). Also, Chantler et al (2022) suggested that improved aerobic tness may decrease the level of splanchnic hypoperfusion (10). Results of our study have shown that in Test II athletes not only nished the exercise test in a shorter time but also achieved higher power which shows an improvement in exercise ability, proving that the aerobic capacity may in uence gut permeability.…”
Section: Discussionsupporting
confidence: 78%